Human rights and healthcare - Wicks, Elizabeth 1973- (Hart Publishing, 2007)
Elizabeth Wicks looks at medical law from a human rights perspective. Almost all issues traditionally taught under a 'medical law' label have significant human rights issues inherent within them. This book brings those human rights issues to the fore.
Bevorzugte Informationsquelle: Landingpage (Bloomsbury Collections), da weder Titelblatt noch Impressum vorhanden
Keywords: Droits de l'homme (Droit international); Médecine - Droit; Éthique médicale; Menschenrecht; Bioethical Issues -- Great Britain; Human Rights -- legislation & jurisprudence -- Great Britain; Human rights; Jurisprudence -- Great Britain; Legislation, Medical -- Great Britain; Medical ethics; Medical laws and legislation; Medizin; Rechtsprechung; Medizinische Ethik; Großbritannien